Merawat Kesehatan Mental dengan Aktivitas Memancing Ikan - Mas Rukhin Lubabul Huda; Fadeli Ehsan Hanafi (Fakultas Dakwah UIN KHAS Jember, 2026)
Maintaining mental health is a necessity and obligation for each individual. Fishing is not just a way to fill spare time or pass the time when unemployed, but also an effort to maintain mental health. This research is important to study in depth the meaning of fishing for people who have a hobby of fishing. The research method used a qualitative method with a descriptive narrative approach with a case study of fishing activities. The research was conducted through direct observation in the field, interviews, and documentation, and was reinforced by various sources of reference books or scientific articles. The results of the study were 1) uncovering the history of fishing, 2) fishing in the open air as an effort to increase calmness. 3) the emotional dynamics of fishing activities with expressions of happiness when catching fish and as a lesson in managing patience because fishing has an element of uncertainty, 4) maintaining mental health through fishing activities, starting with setting aside free time for fishing to achieve psychological well-being for fishing enthusiasts. Fishing as an activity to maintain mental health by fishing in the open air because the open air can be enjoyed beautifully, creating comfort and tranquility as an effort to nurture the mind.